DETERMINASI INDEKS PEMBANGUNAN MANUSIA (IPM), TINGKAT PARTISIPASI ANGKATAN KERJA (TPAK), DAN GINI RASIO TERHADAP TINGKAT KEMISKINAN DI KABUPATEN KEBUMEN - Akbar Taufani, Nihat; Marseto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Human Development Index (HDI), Labor Force Participation Rate (LFPR), and Gini Ratio on the poverty rate in Kebumen Regency during the 2011-2024 period. The study employed a quantitative approach using secondary time-series data obtained from Statistics Indonesia (BPS), analyzed through multiple linear regression with the Ordinary Least Squares (OLS) method. The classical assumption tests indicated that the regression model satisfied the assumptions of normality and was free from multicollinearity, heteroscedasticity, and autocorrelation. The results showed that the Human Development Index had a negative and significant effect on the poverty rate, while the Labor Force Participation Rate and Gini Ratio had no significant partial effects. Simultaneously, the three independent variables significantly affected the poverty rate, with a coefficient of determination (R²) of 0.944, indicating that 94.4% of the variation in poverty could be explained by the model. These findings confirm that improving the quality of human development remains the most effective strategy for poverty alleviation in Kebumen Regency.